Human Nuclear Receptor Heterodimers: Opportunities for Detecting Targets of Transcriptional Regulation Using Yeast - Butt, Tauseef R. (Gene Expr, 2018)
Nuclear receptors are model transcription factors. This highly conserved super family of ligand binding transcription factors includes estrogen, progesterone, retinoic acid, thyroid hormone, vitamin D receptors, and several orphan receptors. Nuclear receptors function as homodimers, heterodimers, or monomers. Human thyroid hormone, retinoic acid, vitamin D, and several orphan receptors prefer to work as heterodimers with retinoic X receptor (RXR). RXR function is regulated by its cognate ligand 9-cis-retinoic acid. In some cases heterodimers of RXR are subject to regulation by two different ligands. Mammalian cells are not entirely suited to study pure heterodimeric functions because they contain a repertoire of endogenous receptors and their ligands. Yeast does not contain nuclear receptors or its ligands. Ligand-dependent function of several human nuclear receptors has been reconstructed in yeast. Yeast can be used as a model system to dissect interaction between various heterodimeric partners. The molecular genetics and the speed of doing the experiments in yeast allows us to rapidly clone mammalian cofactors that prefer to work with different heterodimeric partners. Once the human geneome sequence is complete, we predict that the total number of human nuclear receptors will increase from 150 to 500. Novel and efficient cell-based systems will be needed to understand the function of orphan receptors. Yeast is an ideal system to identify pure heterodimeric partners and discover novel ligands for orphan receptors. The advantages and disadvantages of yeast and mammalian system to study nuclear receptor function are discussed.